Processing and nutrition of fats and oils - Hernandez, Ernesto, 1955- (IFT Press series., 2013)
Processing and Nutrition of Fats and Oils reviews current and new practices of fats and oils production. The book examines the different aspects of fats and oils processing, how the nutritional properties are affected, and how fats interact with other components and nutrients in food products. Coverage includes current trends in the consumption of edible fats and oils; properties of fats, oils and bioactive lipids; techniques to process and modify edible oils; nutritional aspects of lipids; and regulatory aspects, labeling and certifications of fats and oils in foods.